AKUNTANSI POSITIF DAN NORMATIF TERHADAP PRAKTIK EARNINGS MANAGEMENT DALAM KEPUTUSAN STRATEGIS MANAJER: SEBUAH STUDI LITERATUR - Devi Anjelika; Cintia Awindah Sigiro; Erni Mawati Daeli; Hamonangan Siallagan (Komunitas Manajemen Kompetitif, 2026)
Earnings management is a common phenomenon in modern business and accounting, driven by the flexibility managers have in selecting accounting policies. It is closely related to strategic decisions aimed at achieving corporate targets, maintaining earnings stability, securing performance-based incentives, and sustaining investor confidence. This study examines earnings management from the perspectives of Positive Accounting Theory and Normative Accounting Theory using a qualitative literature review of scholarly journals, books, and prior research. The findings indicate that Positive Accounting Theory views earnings management as a rational managerial response to economic incentives and contractual relationships within the firm. In contrast, Normative Accounting Theory argues that such practices may reduce the quality and reliability of financial reporting because they do not always objectively represent the company’s actual economic condition. These contrasting perspectives suggest that earnings management is both a realistic managerial practice in business and a practice that should be carefully regulated to preserve the transparency, credibility, and integrity of corporate financial statements.